Enhanced [18F]fluorodeoxyglucose accumulation in the right ventricular free wall predicts long-term prognosis of patients with pulmonary hypertension: a preliminary observational study. (9th January 2014) - Tatebe, Shunsuke; Fukumoto, Yoshihiro; Oikawa-Wakayama, Minako; Sugimura, Koichiro; Satoh, Kimio; Miura, Yutaka; Aoki, Tatsuo; Nochioka, Kotaro; Miura, Masanobu; Yamamoto, Saori; Tashiro, Manabu; Kagaya, Yutaka; et al.
Abstract: Aims: We have previously demonstrated that [ 18 F]fluorodeoxyglucose (FDG) accumulation is increased in the right ventricular (RV) free wall of patients with pulmonary hypertension (PH), and that this accumulation is ameliorated after the treatment with epoprostenol associated with improvement of haemodynamic overload. The aim of this study was to examine whether enhanced RV FDG accumulation by gated positron emission tomography (PET) has a prognostic impact in patients with PH. Methods and results: We examined the prognostic impact of the RV standardized uptake value (SUV) of FDG-PET corrected for the partial volume effect (cRV-SUV) in 27 patients with PH who underwent gated FDG-PET from March 2001 to June 2004. During the follow-up period of 69 ± 49 (mean ± SD) months, among the 27 patients, 15 showed clinical worsening (CW) and 11 died. FDG-PET examination showed that cRV-SUV was significantly higher in the CW group compared with the non-CW group (10.1 vs. 7.6, P = 0.02). Univariate Cox hazard analysis showed that cRV-SUV was significantly correlated with the time to CW (hazard ratio 1.25, 95% confidence interval 1.04–1.51, P = 0.02), which remained significant even after adjustment of World Health Organization functional class. Kaplan–Meier analysis showed that the patients with cRV-SUV ≥8.3 had poor prognosis compared with those with cRV-SUV <8.3 (log-rank P = 0.005 for time to CW and P = 0.07 for mortality). Conclusion: These results indicate that enhanced FDG accumulation in the RV free wall may be a novel prognostic factor in patients with PH.